Art and sovereignty in global politics - Howland, Douglas ; Lillehoj, Elizabeth ; Mayer, Maximilian (Palgrave Macmillan, 2020)
Contents: Introduction : an interdisciplinary approach to art and sovereignty -- Space and sovereignty : a reverse perspective -- The international movement to protect literary and artistic property -- Dongbei, Manchukuo, Manchuria : territory, artifacts, and the multiple bodies of sovereignty in northeast Asia -- Claims -- Stolen buddhas and sovereignty claims -- Art by dispossession at El Paso Saddleblanket Company : commodification and graduated sovereignty in global capitalism -- Claiming sovereignty through equestrian spectacle in northern Cameroon -- Identity and sovereignty in Asian art cinema : digital diaspora films of South Korea and Malaysia -- Re-viewing sovereignty : North Korean authoritarianism and art -- Sovereignty as performance and video art : citizenship between international relations and artistic representation -- Directions for future research on art, sovereignty, and global affairs.